Bettr Barista: A shot at better lives - WANG, Heli (Institutional Knowledge at Singapore Management University, 2019)
This case is set in 2019, and describes the social-entrepreneurial journey of Bettr Barista (‘BB’), a Singapore-based coffee company. Launched in 2011 as a coffee academy, BB offered disadvantaged women and youth in Singapore a four-month long holistic programme providing barista skills for employability, emotional and physical training for psychological wellbeing, and an internship for learning on the job. At the end of the programme, BB helped the trainees secure employment in the industry. By end-2018, it had trained and placed more than 60 individuals with the support of government bodies, social sector organisations and private sector companies. To support and sustain its social goals, BB undertook for-profit coffee workshops for corporates and individuals, and ran other commercial businesses including a coffee roastery, retail coffee outlets and mobile brew bars. By end-2018, the coffee company had served 397,000 cups of coffee to 212,000 consumers through its cafés and mobile bars, and held more than 430 corporate events. However, in order to be truly sustainable, BB needed to expand internationally as the Singapore market was small and offered limited growth potential. Many of the neighbouring countries, being primarily coffee drinking markets, were attractive options. However, this also raised many concerns, as such a strategy could stretch the company’s already limited financial and managerial resources. BB’s business model was unique to Singapore, and the level of market development, technology, governance structures and government support varied significantly across countries in the region. Would BB have the expertise and resources to change or tweak its approach according to each country’s market dynamics? Additionally, executing the expansion plans would require a comprehensive management structure to be put in place at BB. Could all of this be done without affecting the core values the company stood for? This case will help students understand how a social enterprise differs from for-profit and charity organisations, and how social positioning can help create sustainable competitive advantage. Students will get to compare different analytical tools in assessing a company’s performance and its future prospects. It will also highlight how specific resources and capabilities contribute to the company’s ability to deliver the desired value proposition.